Description of Sharp Violent Wound Pattern among Death Cases at Bhayangkara Hospital Level III Manado in the Period July 2019 – June 2021 - Joana M. Posumah; Johannis F. Mallo; Djemi Tomuka (Universitas Sam Ratulangi, 2022)
Abstract: Sharp violence is an action resulting in injuries to the body surface caused by sharp objects that are commonly found around us, such as knive, razor, and even axe. Sharp violence that causes the victim to lose his/her life becomes a criminal act or a crime against life (murder). According to Biro Pengendalian Operasi, Mabes Polri in 2018 concerning the number of murders in Indonesia, North Sulawesi was in the sixth place. This study aimed to describe the pattern of sharp violent injuries among cases of death victims at the Bhayangkara Hospital Level III Manado during the period July 2019 - June 2021. This was a retrospective and descriptive study using Visum et Repertum data. The results obtained 22 cases of death victims due to sharp violence. Most cases occurred in the period of July 2019 - June 2020 as many as 19 cases (86.4%). The most frequent age group was 21-30 years with eight cases (36.4%), followed by age group 17-20 years (36.4%), and age goups 31-40 years and >50 years (each of 18.2%). Male dominated female cases (18 cases/81.8% and 1 case/18.2%). Type of wound was 100% as stab wound. The location of the most injuries was on the left chest which was 13 victims (59%). In conclusion, cases of violent death were mostly male, aged around 21-30 years old, with a stab wound on the left chest.Keywords: wound pattern; sharp violence Abstrak: Kekerasan tajam merupakan tindakan yang mengakibatkan luka pada permukaan tubuh disebabkan oleh benda tajam yang umum ditemukan, seperti pisau, silet, bahkan kapak. Kekerasan tajam yang menyebabkan korban kehilangan nyawa menjadi suatu tindak pidana kriminal atau kejahatan terhadap nyawa (pembunuhan). Laporan Biro Pengendalian Operasi, Mabes Polri pada tahun 2018 menyatakan bahwa Sulawesi Utara berada di urutan keenam. Penelitian ini bertujuan untuk mengetahui gambaran pola luka kekerasan tajam pada kasus kematian di RS Bhayangkara Tingkat III Manado periode Juli 2019-Juni 2021. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data Visum et Repertum. Hasil penelitian mendapatkan 22 kasus kematian korban kekerasan tajam. Kasus kematian terbanyak terjadi pada periode Juli 2019-Juni 2020 yaitu 19 kasus (86,4%). Kelompok usia terbanyak yaitu 21-30 tahun sebanyak delapan kasus (36,4%), diikuti kelompok usia 17-20 tahun (36,4%), serta 31-40 tahun dan >50 tahun (masing-masing 18,2%). Jenis kelamin didominasi oleh laki-laki (18 kasus/81,8% dan 1 kasus/18,2%). Jenis luka merupakan 100% luka tusuk. Lokasi perlukaan terbanyak di dada sebelah kiri yaitu 13 orang (59%). Simpulan penelitian ini ialah kasus kematian kekerasan tajam sebagian besar berjenis kelamin laki-laki, berusia 21-30 tahun, dengan jenis luka tusak pada dada kiri.Kata kunci: pola luka; kekerasan tajam